Kombinasi persilangan dan seleksi in vitro untuk mendapatkan kultivar unggul kentang - Agus Purwito; GA Wattimena (Jurnal Ilmu Pertanian Indonesia, 2008)
Cultivars Granola  dan Atlantic are the best cultivars so far for farmers, due to it adaptation in Indonesia. Cv Granola is resistant to several important diseases, but the quality is low, thus only produce for vegetable purposes. Cv Atlantic is the best cultivar, in term of productivity and quality. Cv Atlantic is suitable for industry purposes, susceptible to several important diseases. Crossing between both cultivars expected to produce high yielding cultivars and adapted to Indonesian environment. The method used was crossing and germinated the seed then selected in vitro. Each germinated seed was propagated in vitro and considered as clones. In vitro selection was performed through vigour, bacterial wilt and soft rot test, as well as micro tuber production. The result of selectionwas then verified in the field. From thousands of seed germinated producing 12 selected clones, 7 clones of them were showed better then their parent in term of tuberization and micro tuber production. The clones were Atnola 1, Atnola 5, Atnola 3, Atnola 10, Atnola 12, Atnola 24, and Atnola 26. Four clones showed level of resistance better than the parent, namely Atnola 3, Atnola 5, Atnola 8, and Atnola 10. The result of field test showed that the seven clones produced better tuber than the parent Atlantic dan Granola, which were Atnola 5 dan Atnola 10 showed vigour, tuber weight, and better level of resistance, thus will be the candidate of high yielding cultivars.